Effects of Enzyme and Probiotic on the Growth Performance of Broiler Chickens: A Meta-Analysis - Sugiharto, Sugiharto; Setiaji, Asep; Adli, Danung Nur; Sholikin, Muhamad Misbakhul (Jurnal Agripet, 2024)
A meta-analysis was conducted to determine the effects of enzyme and probiotic on the growth performance of broiler chickens. A collection of publications covering the years from 2009 to 2021 was compiled using several keywords, such as enzyme, growth performance, and probiotic. A total of 136 comparisons from 19 in vivo investigations were used to create the final dataset. The data were analyzed using the OpenMEE software, considering the feed additives (enzymes and probiotics) as fixed effects and individual studies as random effects. The result showed an insignificant difference (P0.05) between enzymes and probiotics in terms of improving the body weight gain, feed intake, and feed conversion ratio (FCR) of broilers. In conclusion, both probiotics and enzymes improved broiler performances, such as body weight gain, feed intake and FCR. According to the meta-analysis, the ability of enzymes and probiotics to affect broiler performances was equal.